2012
DOI: 10.1182/blood-2011-10-380774
|View full text |Cite
|
Sign up to set email alerts
|

How I treat childhood CML

Abstract: Chronic myeloid leukemia (CML) is composed of 3% of pediatric leukemias, making evidence-based recommendations difficult. Imatinib has revolutionized the treatment for adult CML by eliminating allogeneic stem cell transplantation for almost all patients in chronic phase. Shown effective in pediatric CML, imatinib and successive tyrosine kinase inhibitors (TKI) have provided more therapeutic options. Because stem cell transplantation has been better tolerated in children and adolescents, the decision to treat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 73 publications
7
76
0
3
Order By: Relevance
“…[1] There is still a role for sibling matched Allo-HSCT in chronic myeloid leukaemia (CML), despite the good long-term survival demonstrated with the use of tyrosine kinase inhibitors. [2] Allo-HSCT is also used as salvage therapy in the treatment of paediatric lymphoma. [3] In 2007, ~150 new cases of leukaemia per annum in children aged <14 years were being captured on the South African Children's Cancer Group registry.…”
Section: Researchmentioning
confidence: 99%
“…[1] There is still a role for sibling matched Allo-HSCT in chronic myeloid leukaemia (CML), despite the good long-term survival demonstrated with the use of tyrosine kinase inhibitors. [2] Allo-HSCT is also used as salvage therapy in the treatment of paediatric lymphoma. [3] In 2007, ~150 new cases of leukaemia per annum in children aged <14 years were being captured on the South African Children's Cancer Group registry.…”
Section: Researchmentioning
confidence: 99%
“…Therefore, the use of imatinib therapy in young patients remains controversial. 31,32 In the present study, we demonstrated that patients treated with ISD HSCT have HRQOL comparable to that of patients treated with imatinib. HSCT remains the only proven cure for CML, and the outcome of HSCT for CML has improved significantly.…”
Section: Discussionmentioning
confidence: 56%
“…This represents about 3-5% of all cases of newly diagnosed childhood leukemia [4]. The clinical course and prognosis are similar to that of adult CML.…”
Section: Discussionmentioning
confidence: 94%
“…The clinical course and prognosis are similar to that of adult CML. However, unlike the adult CML, ionizing radiation and other such environmental predisposing factors have not been shown to have a causal effect in its occurrence [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation